Ketepatan Klasifikasi Status Pemberian Air Susu Ibu (ASI) Menggunakan Multivariate Adaptive Regression Splines (MARS) dan Algoritma C4.5 di Kabupaten Sragen - Yusuf Arifka Rahman; Suparti Suparti; Sugito Sugito (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2016)
The progress of a nation influenced and determined by the level of public health, the indicator of the level of health is determined by nutritional status. Nutrition can be given early, namely breastfeeding to infants. This research aims to compare the classification of exclusive breastfeeding and nonexclusive breastfeeding. It used two methods for classifying a breastfeeding to babies in Sragen subdistrict on 2014, the methods are Multivariate Adaptive Regression Splines (MARS) and C4.5 Algorithm. MARS is nonparametric regression method that use to overcome the high dimension of data that produces accurate prediction and continuous models on knot. C4.5 Algorithm is a way of classifying methods from data mining that use to construct a decision tree. To evaluate the result of classification use Apparent Error Rate (APER) calculation. The best classification result using MARS method is by using the combination of Basis Function (BF)=40, Maximum Interaction (MI)=3, Minimum Obsevation (MO)=3 because it will result on the smallest Generalized Cross Validation (GCV). Classification result using MARS method obtained APER is 19,7674% and 80,2326% of accuracy. Classification result using C4.5 Algorithm obtained APER is 18,6047% and 81,3953% of accuracy. From proportion test, concluded classification that formed by MARS is as good as by C4.5 Algorithm. Keywords: Breastfeeding, Classification, MARS, C4.5 Algorithm